Perinatal maternal complications of preeclampsia-eclampsia - Pinedo, Adolfo (2015)
Objectives: To identify maternal and perinatal complications of preeclampsia and eclampsia. Design: Cross sectional study of 359 cases of pregnant women with preclampsia and eclampsia and their products, diagnosed from July 1 1997 to June 30 1998 at Maria Auxiliadora Hospital. Clinical records were reviewed and maternal and perinatal complications were determined. Frequencies were introduced in a double entry table and compared to a control group consisting of the remaining patients without this disease. A value of p < 0,05 was considered significant. Results: In the five-year interval preeclampsia increased significatively from 7,0% to 10,6%, whereas eclampsia decreased from 0,8% to 0,4%. Maternal complications related to death were HELLP syndrome, DIC, hepatic subcapsular hematoma rupture and cerebral hemorrhage. Perinatal complications were neonatal depression, small for gestational age, neonatal depression and asphyxia, respiratory distress and prematurity. Conclusions: Maternal and newborn complications as a result of preeclampsia and eclampsia occur frequently. The frequency and seriousness of these complications rise as the disease worsens, and as such convulsions have to be prevented and treatment of the disease must be timely, with well established protocols and complete use of drug doses, such as magnesium sulfate.